"Who Lives Well in Russia?": 1994–2013 Monitoring Survey. Issue 5 (2nd November 2019) - Voronin, G. L.; Zakharov, V. Ia.; Kozyreva, P. M.
Abstract : This article analyzes life satisfaction in Russia's population over the last two decades, as well as its determinants, based on OECD methodology and data from the Russian Longitudinal Monitoring Survey of the Higher School of Economics (RLMS-HSE). It shows that in Russia, which during its transformational period went through each phase of the business cycle with high oscillation amplitude, life satisfaction is more closely connected to the main economic indicators than in countries that have not experienced similar economic and social shocks. The way life satisfaction and its main determinants are correlated in Russia is similar to what we see in several other countries, but the specific values and forms of these connections depend on the particular motions of the economic cycle in any given country, as well as the previous path (model) of its development.